2008
DOI: 10.1002/pd.2040
|View full text |Cite
|
Sign up to set email alerts
|

Application of proteomics for the identification of differentially expressed protein markers for Down syndrome in maternal plasma

Abstract: Background Despite the large impact of ultrasonographic and biochemical markers on prenatal screening, the ability to accurately diagnose Down syndrome (DS) is still limited and better diagnostic testing is needed.Methods Plasma from 8 women carrying a DS foetus and 12 with non-DS foetuses matched for gestational age, maternal age and ethnicity, in the second trimester of pregnancy, was analysed by two-dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization time-of-flight mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
2
6

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 33 publications
5
62
2
6
Order By: Relevance
“…Early indications were that parent ion intensities from MALDI analysis were in agreement with those of LC-ESI-MS (Griffin et al, 2001) and that parent and fragment ion intensities between separate runs of normal and diseased samples were consistent with Western blots or ELISA analysis of the same sample fractions (Marshall et al, 2003;Reynolds et al, 2003;Zhang et al, 2004;Malik et al, 2005;Yokoi et al, 2005;Yang et al, 2006;Haqqani et al, 2007;Morgan et al, 2007;Wilson et al, 2007;Barba de la Rosa et al, 2008;Gramolini et al, 2008;Hammerer-Lercher et al, 2008;Hao et al, 2008;Kolialexi et al, 2008;Kulasingam et al, 2008;Luque-Garcia et al, 2008;Marchi et al, 2008;Nicol et al, 2008;Plavina et al, 2008;Reichel, 2008;Xing et al, 2008;Wu et al, 2008a;Wang et al, 2008b;Zhao et al, 2008b;Domae et al, 2009;Fortin et al, 2009). Hence, where there is doubt regarding the best fit of the data, a second method such as accurate parent mass, targeted MS/MS, MRM, synthetic chromatography and spectrometry standards or immunological confirmation may be employed (Marshall et al, 2003;Zhang et al, 2004;Malik et al, 2005;Yokoi et al, 2005;Gao et al, 2005a;Haqqani et al, 2007;Plavina et al, 2007;Sardana,...…”
Section: Agreement Between Biochemical and Mass Spectral Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Early indications were that parent ion intensities from MALDI analysis were in agreement with those of LC-ESI-MS (Griffin et al, 2001) and that parent and fragment ion intensities between separate runs of normal and diseased samples were consistent with Western blots or ELISA analysis of the same sample fractions (Marshall et al, 2003;Reynolds et al, 2003;Zhang et al, 2004;Malik et al, 2005;Yokoi et al, 2005;Yang et al, 2006;Haqqani et al, 2007;Morgan et al, 2007;Wilson et al, 2007;Barba de la Rosa et al, 2008;Gramolini et al, 2008;Hammerer-Lercher et al, 2008;Hao et al, 2008;Kolialexi et al, 2008;Kulasingam et al, 2008;Luque-Garcia et al, 2008;Marchi et al, 2008;Nicol et al, 2008;Plavina et al, 2008;Reichel, 2008;Xing et al, 2008;Wu et al, 2008a;Wang et al, 2008b;Zhao et al, 2008b;Domae et al, 2009;Fortin et al, 2009). Hence, where there is doubt regarding the best fit of the data, a second method such as accurate parent mass, targeted MS/MS, MRM, synthetic chromatography and spectrometry standards or immunological confirmation may be employed (Marshall et al, 2003;Zhang et al, 2004;Malik et al, 2005;Yokoi et al, 2005;Gao et al, 2005a;Haqqani et al, 2007;Plavina et al, 2007;Sardana,...…”
Section: Agreement Between Biochemical and Mass Spectral Methodsmentioning
confidence: 89%
“…The use of propyl sulfate chromatography of intact proteins followed by high resolution, 2D IEF/SDS page gels produced only approximately 300 proteins by MASCOT (Pieper et al, 2003a). Potential biomarkers have been detected using 2D-PAGE methods and in some cases confirmed by independent immunological methods (Dowling et al, 2007;Jackson et al, 2007;White et al, 2007;Barba de la Rosa et al, 2008;Jmeian & El Rassi, 2008;Kim et al, 2008a;Kolialexi et al, 2008;Schlautman et al, 2008;Atkinson et al, 2009;Hamrita et al, 2009). Shifts in observed mass or iso-electric point may reflect physiologically significant processing and or posttranslational modifications (Kapinsky et al, 2001;Johnson et al, 2007).…”
Section: F Two-dimensional Poly Acrylamide Gel Electrophoresis (2d Pmentioning
confidence: 96%
“…The current first trimester combined test is based on enzyme-linked immunosorbent assay (ELISA) methods, which is widely used for quantitative protein measurements. Recently, two-dimensional gel electrophoresis (2-D), tandem mass spectrometry (MS-MS) and bead-based multiplexed immunoassays have been used to identify several potential biomarkers in amniotic fluid and maternal blood (Busch et al, 2005, Kolialexi et al, 2008, Nagalla et al, 2007, Tsangaris et al, 2006, clearly demonstrating the potential of applying proteomics techniques in the quest for new biomarkers. Bead-based multiplexed immunoassays use color-coded tiny beads in up to 100 distinct sets.…”
Section: Future Perspectives and Ongoing Researchmentioning
confidence: 99%
“…One firsttrimester study identified seven potential biomarkers [10] , but in a subsequent validation study only one of the proteins (epidermal growth factor) was significantly decreased in maternal serum from trisomy 21 pregnancies [11] . One second-trimester study provided a list of nine potential biomarkers [9] and one first-trimester study provided a list of 28 potential biomarkers [8] . There were five proteins with commercially available ELISA kits from the list of the first-trimester study [8] which were also in the list of the second-trimester study [9] , and we selected these five proteins for our study (afamin, apolipoprotein E, clusterin, ceruloplasmin and transthyretin).…”
Section: Literature Searchmentioning
confidence: 99%
“…There were five proteins with commercially available ELISA kits from the list of the first-trimester study [8] which were also in the list of the second-trimester study [9] , and we selected these five proteins for our study (afamin, apolipoprotein E, clusterin, ceruloplasmin and transthyretin). In addition, we selected epidermal growth factor [10,11] and two additional proteins with large differences between trisomy 21 and euploid fetuses (fetuin-A and pigment epithelium-derived factor glycoprotein) reported in the first-trimester study [8] , but not in the second-trimester study [9] .…”
Section: Literature Searchmentioning
confidence: 99%